2022
DOI: 10.7759/cureus.30346
|View full text |Cite
|
Sign up to set email alerts
|

Acute Kidney Injury Caused by Renin-Angiotensin System Inhibitors During Minimal Change Disease Treatment

Abstract: A 76-year-old Japanese man with nephrotic syndrome was admitted to our department for treatment. After his admission, he was administered prednisolone (PSL) at 40 mg/day, and a percutaneous renal biopsy was performed. However, on the first day of admission, his urinary protein decreased from 5.05 g/gCr to 1.85 g/gCr. On the fourth day of admission, his urinary protein further decreased to 0.38 g/gCr and the patient developed acute kidney injury (AKI). Renin-angiotensin system (RAS) inhibitors were suspected to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…A study by Arisz et al demonstrated that in patients with nephrotic syndrome, a decrease in GFR induced by indomethacin administration resulted in a greater decrease in urinary protein excretion than the reduction in GFR [ 8 ]. Renin-angiotensin system (RAS) inhibitors, known to reduce intra-glomerular pressure, may also lead to a notable decrease in urinary protein levels when MCNS is complicated by RAS inhibitor-associated AKI [ 19 ]. Reduced intra-glomerular pressure may explain severe AKI in MCNS, but it does not account for the abrupt increase in sCr levels observed in our patient, correlating with increased urinary total protein excretion.…”
Section: Discussionmentioning
confidence: 99%
“…A study by Arisz et al demonstrated that in patients with nephrotic syndrome, a decrease in GFR induced by indomethacin administration resulted in a greater decrease in urinary protein excretion than the reduction in GFR [ 8 ]. Renin-angiotensin system (RAS) inhibitors, known to reduce intra-glomerular pressure, may also lead to a notable decrease in urinary protein levels when MCNS is complicated by RAS inhibitor-associated AKI [ 19 ]. Reduced intra-glomerular pressure may explain severe AKI in MCNS, but it does not account for the abrupt increase in sCr levels observed in our patient, correlating with increased urinary total protein excretion.…”
Section: Discussionmentioning
confidence: 99%